Bromodomain and Extra-Terminal Inhibitor BMS-986158 Reverses Latent HIV-1 Infection In Vitro and Ex Vivo by Increasing CDK9 Phosphorylation and Recruitment - Xu-Sheng Huang; Ren-Rong Tian; Meng-Di Ma; Rong-Hua Luo; Liu-Meng Yang; Guang-Hui Peng; Mi Zhang; Xing-Qi Dong; Yong-Tang Zheng (MDPI AG, 2022)
Latent reservoir persistence remains a major obstacle for curing human immunodeficiency virus type 1 (HIV-1) infection. Thus, strategies for the elimination of latent HIV-1 are urgently needed. As a bromodomain and extra-terminal (BET) inhibitor, BMS-986158 has been used in clinical trials for advanced solid tumors and hematological malignancies. Here, we found that BMS-986158 reactivated latent HIV-1 in three types of HIV-1 latency cells in vitro, and in combination antiretroviral therapy (cART)-treated patient-derived peripheral blood mononuclear cells ex vivo, without influencing global immune cell activation. BMS-986158 reactivated latent HIV-1 by increasing phosphorylation of CDK9 at Thr186 and promoting recruitment of CDK9 and RNA polymerase II to the HIV-1 long terminal repeat in J-Lat cells. Furthermore, BMS-986158 exerted strong synergism in reactivating latent HIV-1 when combined with prostratin and vorinostat and enhanced the antiviral activity of anti-HIV-1 drugs. Finally, BMS-986158 showed antiviral activity in an HIV-1 acute infection model, possibly by arresting the cell cycle in infected cells. Thus, these results suggest that BMS-986158 is a potential candidate for AIDS/HIV-1 therapy.